2007
DOI: 10.1093/ps/86.11.2309
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Responses to Selection for Increased Intramuscular Fat in a Chinese Quality Chicken Line

Abstract: The correlated response in traits encompassing meat quality, carcass, sexual maturity, egg production, and egg quality traits arising from selection for increased intramuscular fat (IMF) content of breast muscle were investigated in the fifth generation of a selection experiment including a line (F) selected for increased IMF and a randombred control line (C). The results showed that breast muscle IMF content in the F line (4.25%) was significantly higher (P < 0.001) than that in the C line (3.80%) after 5 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 23 publications
4
69
0
2
Order By: Relevance
“…We also found that the abdominal fat content expressed as the percentage BW was significantly (P , 0.02; Table 3) lower with the 0.25% and 1.00% L-Arg treatments compared with the control, whereas they did not differ significantly from each other. IMF is one of the major factors that affects meat quality because of its effects on other traits such as the flavor, juiciness and tenderness of meat (Zhao et al, 2007). The abdominal fat tissue grows faster compared with other fat tissues (Butterwith, 1989) and it reaches its maximum rate of growth at 42 days of age (Havenstein et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the abdominal fat content expressed as the percentage BW was significantly (P , 0.02; Table 3) lower with the 0.25% and 1.00% L-Arg treatments compared with the control, whereas they did not differ significantly from each other. IMF is one of the major factors that affects meat quality because of its effects on other traits such as the flavor, juiciness and tenderness of meat (Zhao et al, 2007). The abdominal fat tissue grows faster compared with other fat tissues (Butterwith, 1989) and it reaches its maximum rate of growth at 42 days of age (Havenstein et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The right breast muscles were removed from the sternum, minced after removing any obvious fat, and stored at 2208C. The IMF of the breast muscle was determined in triplicate, according to the method described by Zhao et al (2007), and expressed as the percentage total fat (dry weight). Blood samples were collected using a 5-ml anticoagulant syringe (Shanghai K & G International Co. Ltd, Shanghai, China) via the wing vein, centrifuged at 48C and 5900 3 g for 10 min to obtain the plasma, and stored in 1.5-ml Eppendorf tubes at 2708C until analysis.…”
Section: Performance Parametersmentioning
confidence: 99%
“…Increased IMF is generally associated with decreased shear values and thus with improved meat tenderness. Zhao et al (2007) reported that an increase of IMF resulted in a significant decrease of shear values in chickens. A negative correlation between IMF and shear values has also been found in pigs (Van Laack et al, 2001) and sheep (Okeudo and Moss, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve birds were sacrificed per week at 4, 8, and 16 weeks of age, and the thigh muscles were collected. The right thigh muscles collected from the 12 birds sacrificed each week were stored at −20°C to determine intramuscular fat (IMF) content by ether extraction in a Soxhlet apparatus (Zhao et al, 2007), which was expressed as a the percentage of muscle weight (on dry matter basis). The left thigh muscles collected from the same birds were stored at −80°C for RNA extraction.…”
Section: Use Of Birdsmentioning
confidence: 99%
“…It is generally accepted that intramuscular fat (IMF) content is an important indicator of meat quality (Zhao et al, 2007;Choi & Kim, 2009;Hocquette et al, 2010). The problems of meat quality, such as sensory characteristics, tenderness and physical attributes, are related to fat accumulation in broilers.…”
Section: Introductionmentioning
confidence: 99%